Development of Canva-Based Digital Physics Worksheets on Motion to Enhance Students' Scientific Literacy - Eni Sumanti Nasution; Sri Utami Kholilla Mora Siregar; Kasmawati; Randy Sanjaya; Ferawati Artauli Hasibuan (Postgraduate, University of Mataram, 2026)
This study aimed to develop and evaluate a Canva-based Digital Student Worksheet (LKPD) on motion concepts to improve students’ scientific literacy. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation phases. Product feasibility was assessed through expert validation, while effectiveness was evaluated through limited field trials (n = 10) and large field trials (n = 20) conducted during the implementation phase. Scientific literacy was measured using PISA-based test items covering the dimensions of scientific content, context, and competency. The developed LKPD achieved a validity score of 93.8% (very valid). Practicality scores reached 94.0% from teachers and ranged from 90.5% to 94.5% from students, indicating a very practical category. The effectiveness evaluation revealed substantial improvements in students’ scientific literacy, with the greatest gains observed in the scientific competency dimension, particularly in explaining scientific phenomena and interpreting data related to motion concepts. N-Gain scores reached 0.71 in the limited field trial and 0.75 in the large field trial, both categorized as high. These findings indicate that the Canva-based digital LKPD is valid, practical, and effective for supporting interactive physics learning and enhancing students’ scientific literacy in secondary education.